Immunization with Hexon modified adenoviral vectors integrated with gp83 epitope provides protection against Trypanosoma cruzi infection. - Anitra L Farrow; Girish Rachakonda; Linlin Gu; Valentina Krendelchtchikova; Pius N Nde; Siddharth Pratap; Maria F Lima; Fernando Villalta; Qiana L Matthews (Public Library of Science (PLoS), 2014)
Trypanosoma cruzi is the causative agent of Chagas disease. Chagas disease is an endemic infection that affects over 8 million people throughout Latin America and now has become a global challenge. The current pharmacological treatment of patients is unsuccessful in most cases, highly toxic, and no vaccines are available. The results of inadequate treatment could lead to heart failure resulting in death. Therefore, a vaccine that elicits neutralizing antibodies mediated by cell-mediated immune responses and protection against Chagas disease is necessary.The "antigen capsid-incorporation" strategy is based upon the display of the T. cruzi epitope as an integral component of the adenovirus' capsid rather than an encoded transgene. This strategy is predicted to induce a robust humoral immune response to the presented antigen, similar to the response provoked by native Ad capsid proteins. The antigen chosen was T. cruzi gp83, a ligand that is used by T. cruzi to attach to host cells to initiate infection. The gp83 epitope, recognized by the neutralizing MAb 4A4, along with His6 were incorporated into the Ad serotype 5 (Ad5) vector to generate the vector Ad5-HVR1-gp83-18 (Ad5-gp83). This vector was evaluated by molecular and immunological analyses. Vectors were injected to elicit immune responses against gp83 in mouse models. Our findings indicate that mice immunized with the vector Ad5-gp83 and challenged with a lethal dose of T. cruzi trypomastigotes confer strong immunoprotection with significant reduction in parasitemia levels, increased survival rate and induction of neutralizing antibodies.This data demonstrates that immunization with adenovirus containing capsid-incorporated T. cruzi antigen elicits a significant anti-gp83-specific response in two different mouse models, and protection against T. cruzi infection by eliciting neutralizing antibodies mediated by cell-mediated immune responses, as evidenced by the production of several Ig isotypes. Taken together, these novel results show that the recombinant Ad5 presenting T. cruzi gp83 antigen is a useful candidate for the development of a vaccine against Chagas disease.